2016
DOI: 10.1585/pfr.11.2402056
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Termination Process of Long Pulse Plasma Discharges Using Stereoscopic Fast Framing Cameras in the Large Helical Device

Abstract: Long pulse discharges in the Large Helical Device (LHD) were interrupted by the emission of large amounts of carbon dusts released from a closed helical divertor in the previous experimental campaign (FY2013). In order to control the dust emission, the configuration of the closed divertor near lower and upper ports was modified in the last experimental campaign (FY2014). While the modification of the divertor configuration has successfully controlled the release of dusts, long pulse discharges were often termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The surface temperature of the vacuum vessel and the divertor components are set to 300 and 500 K, respectively. The iron dust source is located on the surface of a helical coil and can be in the inboard side of the torus, which was identified by the observation with the stereoscopic fast framing camera . The poloidal cross‐section of a typical plasma density profile in the peripheral plasma at the toroidal angle at which the iron dust source exists (toroidal angle ϕ = 10.625°) is also presented.…”
Section: Set‐up Of Impurity Transport Simulation In the Lhd Peripheramentioning
confidence: 99%
See 1 more Smart Citation
“…The surface temperature of the vacuum vessel and the divertor components are set to 300 and 500 K, respectively. The iron dust source is located on the surface of a helical coil and can be in the inboard side of the torus, which was identified by the observation with the stereoscopic fast framing camera . The poloidal cross‐section of a typical plasma density profile in the peripheral plasma at the toroidal angle at which the iron dust source exists (toroidal angle ϕ = 10.625°) is also presented.…”
Section: Set‐up Of Impurity Transport Simulation In the Lhd Peripheramentioning
confidence: 99%
“…While some long pulse discharges were terminated by carbon dust emission from the divertor region, which were caused by the exfoliation of carbon‐rich mixed material deposition layers accumulated near the divertor plates (isotropic graphite), some long pulse discharges were interrupted by the iron dust emission from the surface on helical coil cans (stainless steel) just after the appearance of sparks (arcing). An observation with a stereoscopic fast framing camera revealed that iron dust released from the arcing point penetrated into the main plasma confinement region, causing the radiation collapse …”
Section: Introductionmentioning
confidence: 99%
“…It clearly evidences that most significant dust events are observed in disruptive shots, or in the very first shots after a disruption: on a total of 344 fast camera movies with more than 10 dust events, 209 correspond to disruptive shots and 40 to shots immediately preceded by a disruption. Several basic mechanisms can link dust to disruptions: i) dust may be produced by transient heat loads on the PFCs during the disruption [27], ii) dust previously deposited onto the PFCs might be remobilized during the disruption by thermal shocks, by mechanical vibrations of the PFCs or by forces due to large currents induced by fast transients [27,28] and iii) disruption might be due to the presence of an excessive amount of dust in the plasma [3]. It is nearly impossible to say whether dust is produced or only remobilized during a given disruption when analyzing fast video data.…”
Section: A Main Tendenciesmentioning
confidence: 99%
“…These processes damage and erode the PFCs and limit their lifetime, making it sometimes necessary to procede to maintenance shutdowns to replace the damaged components. The erosion of PFCs also leads to the formation of dust, which can potentially cause several operational concerns: for instance, dust migration in the vessel and the related release of impurities to the hot core plasma is responsible for high core radiation, which reduces the performance of fusion plasmas and may cause disruption, particularly in long pulse discharges [3]; dust accumulation may also degrade mirrors and diagnostics, or lead to erroneous temperature measurements of the PFCs. The DITS campaign on Tore Supra suggests that dust may be an operational limit if a fixed plasma scenario is used repeatedly [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…For adopting the tungsten divertor, there is a concern about the sustainment of long pulse discharges. That is, electric arcing on the surface of the vacuum vessel has been frequently observed during the plasma discharges with abrupt increase in the iron ion intensity in the plasma, where large amounts of iron dust were released by the electric arcing [3]. The dust enters the peripheral plasma, and iron ions are produced because iron is the main component of the vacuum vessel (SUS316L).…”
Section: Introductionmentioning
confidence: 99%